О словообразовательных вариантах в русском языке XVII века - Cудавичене, Л. (Kalbotyra, 1980)
The presence of derivative variants in the Russian version of the Lithuanian Statute, with its abundance of suffixed forms, manifests the richness of the word-building system of the language of the text. The variation of two, sometimes even three words, with identical meaning, but derived by means of different suffixes, regularly from one and the same root, was eliminated by the choice of such words which later on were fully intergrated into the lexical system of the Russian language. Naturally, such choice can be accounted for by definite factors. A great importance should be attached in this to language standardization (if it is possible to speak of standard with reference to the Old Russian literary language).